The Effects of 15 or 30 s SIT in Normobaric Hypoxia on Aerobic, Anaerobic Performance and Critical Power - Karabiyik, Hakan; Eser, Mustafa Can; Guler, Ozkan; Yasli, Burak Caglar; Ertetik, Goktug; Sisman, Aysegul; Koz, Mitat; Gabrys, Tomasz; Pilis, Karol; Karayigit, Raci (MDPI AG, 2021)
Sprint interval training (SIT) is a concept that has been shown to enhance aerobic-anaerobic training adaptations and induce larger effects in hypoxia. The purpose of this study was to examine the effects of 4 weeks of SIT with 15 or 30 s in hypoxia on aerobic, anaerobic performance and critical power (CP). A total of 32 male team players were divided into four groups: SIT with 15 s at FiO2: 0.209 (15 N); FiO2: 0.135 (15 H); SIT with 30 s at FiO2: 0.209 (30 N); and FiO2: 0.135 (30 H). VO2max did not significantly increase, however time-to-exhaustion (TTE) was found to be significantly longer in the post test compared to pre test (p = 0.001) with no difference between groups (p = 0.86). Mean power (MPw.kg) after repeated wingate tests was significantly higher compared to pre training in all groups (p = 0.001) with no difference between groups (p = 0.66). Similarly, CP was increased in all groups with 4 weeks of SIT (p = 0.001) with no difference between groups (p = 0.82). This study showed that 4 weeks of SIT with 15 and 30 s sprint bouts in normoxia or hypoxia did not increased VO2max in trained athletes. However, anerobic performance and CP can be increased with 4 weeks of SIT both in normoxia or hypoxia with 15 or 30 s of sprint durations.
Keywords: Male; chronic training; Team athletes; team athletes; HIIT; normobaric hypoxia; High-Intensity Interval Training; sprint duration; Adaptation, Physiological; Normobaric hypoxia; Article; Oxygen Consumption; Athletes; Humans; Anaerobiosis; Chronic training; Hypoxia; Sprint duration; 1. No poverty; 3. Good health